Analisis Efektifitas Lembaga Pengelola Hutan Nagari Dalam Mencapai Tujuan Program Perhutanan Sosial Dan Faktor-Faktor Yang Mempengaruhinya : (Studi Kasus Hutan Nagari Pakan Rabaa Dan Hutan Nagari Pasir Talang Timur Kabupaten Solok Selatan) - Laila Fitria; Yonariza; Ardinis Arbain (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
His study aims to examine the effectiveness of the Nagari Forest Management Institution in achieving the objectives of the Social Forestry Program and examine the factors that influence the effectiveness of the Nagari Forest Management Institution in achieving the objectives of the Social Forestry Program. This research is a qualitative research using interviews, observations and FGDs to collect research data. The results of this study indicate that the Nagari Forest Management Institute in implementing the Social Forestry program from an ecological aspect has been effective, this can be seen from changes in the behavior of exploitative permit holders to care about forests, permit holders have played an active role in preserving and protecting forests, namely by planting replanting forest plants in agroforestry manner so as to have a positive impact on the environment in the form of maintaining water sources, uprooting critical land, conserving biodiversity, and reducing forest fires, so that forest sustainability is maintained. Furthermore, the Nagari Forest Management Agency in the economic aspect is considered ineffective because the social forestry program has not been able to increase the amount of production generated from business activities, the amount of net profit and business expansion and this program has not opened up many business opportunities for permit holders. Then the authors also found that not all of the Social Forestry Business Institutions formed at LPHN could operate and carry out transactions and the ability to access permit holders in marketing Non-Timber Forest Product products was also still low. The Nagari Forest Management Institution in the social aspect is also ineffective where the LPHN has not been able to increase the knowledge of permit holders, as seen from the lack of participation of LPHN members in every activity and the lack of strong institutional capacity. LPHN has also not been able to provide satisfaction to permit holders with the results achieved, and has not had an impact on farmers